2001
DOI: 10.1074/jbc.m009633200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SWI·SNF Complex Subunit BAF60a as a Determinant of the Transactivation Potential of Fos/Jun Dimers

Abstract: Fos family proteins form stable heterodimers with Jun family proteins, and each heterodimer shows distinctive transactivating potential for regulating cellular growth, differentiation, and development via AP-1 binding sites. However, the molecular mechanism underlying dimer specificity and the molecules that facilitate transactivation remain undefined. Here, we show that BAF60a, a subunit of the SWI⅐SNF chromatin remodeling complex, is a determinant of the transactivation potential of Fos/Jun dimers. BAF60a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 31 publications
8
117
0
Order By: Relevance
“…When CD44 and collagenase cDNA probes were used for the nuclear run-on assay, active transcription was detectable in nuclei isolated from MDA-MB435, whereas no signal was detected in those from SW13(vim-) (Figure 1b). These results are consistent with the observation that SW13(vim-) cells never express both of two genes at the transcriptional level (Ito et al, 2001;YamamichiNishina et al, 2003), confirming that the run-on transcription assay faithfully reflects transcriptional activity in these cells.…”
Section: Cell Linesupporting
confidence: 90%
See 1 more Smart Citation
“…When CD44 and collagenase cDNA probes were used for the nuclear run-on assay, active transcription was detectable in nuclei isolated from MDA-MB435, whereas no signal was detected in those from SW13(vim-) (Figure 1b). These results are consistent with the observation that SW13(vim-) cells never express both of two genes at the transcriptional level (Ito et al, 2001;YamamichiNishina et al, 2003), confirming that the run-on transcription assay faithfully reflects transcriptional activity in these cells.…”
Section: Cell Linesupporting
confidence: 90%
“…These interacting proteins include products of proto-oncogenes such as c-fos, c-jun (Ito et al, 2001), and c-myc (Cheng et al, 1999), and tumor suppressor proteins such as Rb (Dunaief et al, 1994;Trouche et al, 1997;Strobeck et al, 2000), p53 , and b-catenin (Barker et al, 2001). We previously reported that the heterodimer of c-Fos and c-Jun requires functional SWI/SNF complex for transactivation through AP-1 DNA binding sites (Ito et al, 2001). Therefore, this complex would be involved in multiple processes associated with formation or suppression of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…BAF60a was initially identified as a determinant of the transactivation potential of Fos/Jun dimers to induce the endogenous AP-1-regulated genes such as collagenase and c-met. 32 Its function was further described as a mediator of the antitumor effects of p53, 33 a regulator of hepatic lipid metabolism, 24 and an androgen receptor cofactor that modulates TMPRSS2 expression. 34 This suggests a pleiotropic role of BAF60a in cellular and organismal biology by integrating endocrine, metabolic, and circadian signals.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the actual response of a promoter to changes in Jun activity will depend on multiple parameters, including the activity of the Jun dimer partner, other transcription factors and coactivators acting on the promoter, and the promoter architecture (Falvo et al, 2000;Wathelet et al, 1998). In this respect it should be noted that the Jun, Fos and ATF family members di er in their ability to directly or indirectly interact with the CBP/p300 family of transcriptional co-activators, the Jab1 co-activator, and Swi/Snf chromatin remodeling factors (Lee et al, 1996;Duyndam et al, 1999;Claret et al, 1996;Kawasaki, 1998;Kawasaki et al, 2000;Ito et al, 2001).…”
Section: Transformation and Jun-dependent Transcriptional Controlmentioning
confidence: 99%